Multicultural Education in the Era of Society 5.0 - Saidah; Hikmah, Nur (IJER (Indonesian Journal of Educational Research), 2023)
The aim of this research is to describe multicultural education in the era of society 5.0. This research is library research, examining sources that discuss multicultural education and society 5.0. The research results show that in the era of society 5.0, there is a variety of diversity (pluralism), especially in the field of education. Diversity in the world of education includes gender, ethnicity, culture, and religion. Apart from that, in the educational process, there is also a diversity of potential, intelligence, talents, interests, motivations, and so on. There is also diversity in educational media, whether hardware or shopware. There is also diversity in the use of communication and information technology in education. The use of computers and the internet (digital) in the educational process also varies according to the needs and abilities of educators, students, and educational institutions. So multiculturalism in the field of education in society 5.0 is an unavoidable necessity.